Peran Trichoderma reesei E. G Simmons pada Pengendalian Damping-Off Semai Cendana (Santalum Album Linn.) - S. M. Widyastuti; M. Hariani (Universitas Gadjah Mada, 2006)
The sandalwood seedling has been planted in the nursery of Balitbang Kehutanan NTT to experience the destruction is about 20%, seedling is attacked by damping-off. Biological control has been developed as alternate method against soil born diseases to eliminate damage on the environment. One of the biological agents having high antagonistic potential against soil born pathogen is Trichoderma spp. The direction of experiment to search the cause of lodoh on the sandalwood seedling and the application influences T. reesei on the control lodoh in the sandalwood seedling. Methods of the experiment was (1) isolation the sandalwood seedling of painful and soil example from NTT, (2) Postulat Koch test on the sandalwood seedling, (3) antagonistic test of T. reesei in vitro and (4) effectiveness test of T. reesei against developing patogen in vivo. The result indicated that lodoh on the sandalwood seedling caused by Fusarium sp. T. reesei in vitro inhibited Fusarium sp. at average of 100% accordingly. The application of T. reesei as biological control agent against Fusarium sp. showed high effectivity. The attact percentage of lodoh on sandalwood seedlings showed that the lowest one was growth on compost formulated with T. reesei (5%), whereas seedlings growth on compost without T. reesei, unsteril sands and soil samples from NTT were 30%, 35% and 65%.